Complicaciones severas en infecciones odontogénicas. - Cudco Coro, María Isabel (2024)
The present study focuses on analyzing the frequency and severity of complications resulting from dental infections. Lack of oral hygiene and systemic conditions such as diabetes are identified as risk factors, which increase the likelihood of serious complications. A systematic review methodology based on the PRISMA method is used, which focuses on a PICO question to delineate the clinical range and the critical complications identified. The sample analysed consists of individuals who have been diagnosed with dental infections. The data used was obtained from recognised databases such as PubMed and ScienceDirect. Strict inclusion and exclusion criteria were applied to ensure that the information was relevant and up-to-date. The results highlight the high frequency of complications such as necrotizing fasciitis and descending necrotic mediastinitis, which underlines the importance of early diagnosis and effective treatment to slow the progression of the infection. It concluded that the implementation of a proactive approach and the promotion of oral hygiene education are crucial to reducing the incidence of serious cases. The need for further research is suggested in order to improve intervention and therapeutic strategies in the field of dentistry.